Coronavirus Disease 2019 (COVID-19) Lockdown: Morbidity, Perception, Behaviors, and Attitudes in French Families From the PARIS Birth Cohort - Citerne, Antoine; Rancière, Fanny; Roda, Célina; Momas, Isabelle (Frontiers in Public Health, 2022)
Background Few studies have examined the overall experience of adolescents and their families during COVID-19 lockdowns. This study describes COVID-19-related morbidity in the PARIS birth cohort families during the first lockdown in France and identifies family profiles in terms of morbidity, perception, behaviors, and attitudes. Methods Online questionnaires were sent to adolescents of the PARIS birth cohort and their parents. Possible COVID-19 was defined by symptoms using the ECDC definition. Household transmission was estimated by calculating the observed clinical secondary attack rates. Perception, behaviors and attitudes were assessed by levels of stress, degree of satisfaction regarding levels of information about COVID-19, degree of agreement with the lockdown and preventive measures. COVID-19 morbidity in adolescents and parents was compared using chi-squared or Student's t-tests. Within each family, perception, behaviors, and attitudes were compared between adolescents and parents using matched-pairs tests. To identify contrasting family profiles, a K-means cluster analysis was implemented. Results Of 1,549 families contacted, 1,051 (68%) participated. Adolescents were less affected by possible COVID-19 than their parents (138.7 vs. 192.7 per 1,00,000 person-days). Household transmission of possible COVID-19 was higher when possible COVID-19 came from adults than from adolescents. Most families implemented preventive measures. Adolescents and parents generally shared the same attitudes, but adolescents were less compliant with restrictive measures. Four family profiles were identified which differed mainly regarding family stress, COVID-19 in the household, and compliance with preventive measures. Conclusion Improving information dissemination to parents and adolescents, including dedicated adolescent messages, would increase adherence to preventive measures.